Strategi Global Civil Society di Level Lokal: Kasus Earth Hour Malang - Najamuddin Khairur Rijal; Palupi Anggraheni (Intermestic: Journal of International Studies, 2019)
This article examines Earth Hour Malang as a strategy of global civil society at the local level in campaigning green living and encouraging public awareness for the environment. By using global civil society conceptualization, visibility, and audibility strategies, primary data was collected through interviews with Earth Hour Malang activists as well as documentation studies on various Earth Hour Malang’s social media, also supported with secondary data. The results indicates that Earth Hour Malang carries out an active, consistent and continuous visibility and audibility strategy by taking various direct actions (offline) and online through various instruments, such as social media, radio, video, and television. This article contributes to studies related to the existence of global civil society at the local level.